PERAN LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP PRESTASI KERJA PEGAWAI DI KANTOR DINAS KESEHATAN KOTA METRO - Daniel, Daniel; Febriyanto, Febriyanto; Riyanto, Kuncoro Budi (SIMPLEX: Journal of Economic Management, 2025)
Efforts to improve and improve the quality of the working environment in the Metro City Health Service Office, such as providing adequate work facilities, creating a comfortable and conducive working environment, as well as improving communication and cooperation between staff. So the purpose of this study is to test the work environment and satisfaction of both partially and simultaneously with the performance of the work at the Metro Health Service office. The study uses a quantitative calculation method of the kind of survey questionnaire distributed to the entire staff using a google form distributed with the staff and found as many as 59 respondents. Data analysis techniques using validity tests, reliability tests, and decision-making using partial tests (t), simultaneous tests (f), and determination coefficients. The results of the analysis prove that 1) If the conditions and atmosphere in the workplace can affect the ability of a person in performing tasks and achieving the desired results. A positive, supportive and motivating working environment can improve the performance of employees, while a negative or unfavourable environment can have a negative impact on their performance. When an employee is satisfied with his job, favourable conditions for better performance can be created. 3) If we can create conditions that enable staff to ensure optimal and sustainable health care. By creating a good working environment and striving to increase job satisfaction, organizations can drive optimal performance and greater contribution to the public health mission. Recommendation that the researcher gave among them 1) to the highest leader to be able to pay attention to the details of the aspect of the workplace so that the increasingly dense working environment in the middle of this City can be focused and comfortable in carrying out the work activity. 2) to the senior leader to pay more attention to variables of job satisfaction on the aspects of the job itself, it means each employee to be more attentive in performing the tasks already assigned. 3) It is recommended to the top leader to take note of the intellectual ability of the employee whenever there is recruitment for the candidate honourable and candidate ASN